A democracia da eficiência e o retrocesso social - Belegante, Denilson (2018)
Fundamental rights, like the achievements of humanity, have emerged slowly and gradually with the advent of Modernity, which has allowed for a positive change in national and international legal systems. However, in spite of such positivation, the implementation of them, especially the social ones, has been difficult, taking into account the neoliberal creed that overvalues the principle of freedom, to the detriment of the principle of equality. So, in order to confront this question, there is a need to reconcile the principles of freedom and equality, as well as to rescue the principle of fraternity (solidarity), which can only be achieved through democratic, guaranteeing, participatory and inclusive rights reconstruction. fundamental rights, so that the most vulnerable and those in need of social inclusion are favored. In order to do so, a new understanding of contemporary democracy is required, since it is still markedly elitist and restricted, by privileging the market and the economy in the political decisions of the government, relegating them to the technicians in the name of economic efficiency. This view was also supported by the theory of elites, which supported elite democracy, in which only the elite could participate in government, given that the masses did not know politics. Likewise, the narrow view of democracy linked democracy to elections as the form of participation, limiting it to a competition of voter votes. The economic theory of democracy, backed by the economic analysis of law, in a marginalist and neoliberal view of the economy, devoid of ethical content and based on homo oeconomicus, starts to dictate the model of contemporary democracy, in which government decisions must follow the dictates of the economy and the market, implying fundamental rights at risk as they cease to be realized in the name of economic efficiency. This modality of democracy, promoted by the current Brazilian government, as a democracy of efficiency, was practically implemented with the enactment of Constitutional Amendment 95/2016, by instituting a 20-year freeze on investments in social areas, such as health, education and social assistance, as a form of contingency of public spending, with the adoption of a strict fiscal adjustment. These measures, as reflected in the realization of fundamental social rights, these being included as stony clauses, in the norm of art. 60, § 4, IV, of the Federal Constitution, imply a violation of these clauses, as well as impose an obvious social retrogression, in clear violation of the principle of the prohibition of social retrogression, implicitly recognized by the Brazilian constitutional order. T herefore, as a counter to this retrocession implemented by the referred Amendment, there must be a constitutional interpretation committed to the constitutional identity, which is the guarantor of fundamental rights, including social ones, which must be placed in the sphere of the undecidable, safe from majorities, preventing them from being reached, under penalty of unconstitutionality.